Evaluation of plant and animal products against Chilo partellus Swinhoe (Lepidoptera: Crambidae) infestation in sorghum field - Adem Nega; Emana Getu (PLoS ONE, 2025)
Plant and animal products with optimum concentrations were synthesized and evaluated against Chilo partellus Swinhoe infestation in the sorghum field. The experiment was designed in a randomized complete block design in a factorial arrangement with three replications. The treatments were M. ferruginea aqua extract, Cow urine, and a mixture of M. ferruginea and Cow urine each at three rates of concentration (5%, 10%, and 15%). Treatments were applied at two levels of frequencies (2 and 3 times application). The pest infestations and all its activities were systematically screened as well. Results indicated that all formulations significantly (P<0.01) reduced damage at the highest rates with three times applications. The mixture treatments were most effective in reducing leaf damage, dead hearts and the pest infestations with significant larval mortality at a higher rate with three times applications. No larvae per plant were recorded on sorghum treated with M. ferruginea aqua extract at a higher rate in three applications. Likewise, the highest mortality was recorded at the higher rate (15% concentration) of the mixture. Application rates and frequencies of all treatments were positively correlated to larval mortality. M. ferruginea aqua extract and the mixture were negatively correlated while cow urine has no relation to the density of larvae. Significantly taller plants, a smaller number of holes per plant, and the shortest tunnel length were recorded from the mixture, and M. ferruginea aqua extract treated plots at a higher rate and two times more applications. Best grain yields and yield advantages were recorded at three times applications of the higher rates. In conclusion, plant and animal-based insecticides at the higher rates with three times applications were best in reducing C. partellus infestations in the field. Likewise, their effect on the main natural enemy of the pest was minimal.